Preeclampsia, Eclampsia, and Adverse Maternal and Perinatal Outcomes: A Secondary Analysis of the World Health Organization Multicountry Survey on Maternal and Newborn Health. Issue 1 (March 2015) - Abalos, E.; Cuesta, C.; Carroli, G.; Qureshi, Z.; Widmer, M.; Vogel, J.P.; Souza, J.P.
Abstract : ( BJOG . 2013;121(suppl 1):14–24)